Exploring the Linguistic Obstacles in Mastering English Tenses: A Study of Non-English Major University Students’ Perceptions - Engelina Salainti; Alfrits Roul Sinadia (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
In the Indonesian higher education context, non-English major students often encounter difficulties in mastering English tenses. This study aims to investigate students’ perceptions of the cognitive, affective, and behavioral challenges they experience when learning English tenses. A quantitative descriptive design was employed, and data were collected through a 5-point Likert scale questionnaire administered to 65 non-English major students at Universitas Klabat (UNKLAB), representing various faculties such as Computer Science, Business, and Nursing. The findings reveal a complex interaction between linguistic and psychological factors. From a cognitive perspective, 40% of the students identified the absence of a tense system in the Indonesian language as a major obstacle, indicating L1 interference. Affectively, 63% of the participants perceived English tenses as the most difficult aspect of learning English, while 49% reported reduced confidence in speaking due to fear of making grammatical errors. Behaviorally, 65% of the students demonstrated an avoidance strategy by frequently using the simple present tense to minimize mistakes. Despite these challenges, 77% of the students recognized the importance of mastering tenses for their future professional needs. These findings highlight the need for contextualized and communicative grammar instruction that addresses both linguistic difficulties and learners’ emotional barriers in non-English major EFL classrooms.